Natural durability of rubberwood(Heva brasiliensis) under marine conditions - Santhakumar L N; Srinivasan V V (Rubber Board Bulletin, 1990)
Wood from Hevea brasiliensis(Willd. ex Adr. de Juss.) Muell. Arg., the Para rubber tree, is widely used at present in packing cases, match industry and also as firewood. This plantation raw material is now available in large quantities. However, for the effective utilisation of this timber, steps should be taken to diversify its uses as a construction material including marine structures. The present paper deals with the natural durability of rubber wood against marine borers in Goa waters. Test panels of rubber wood were completely destroyed within a short period of seven months due to severe attack by marine borers indicating their very low natural resistance. Wood borers encountered were Martesia striata Linnaeus, Nausitora hedleyi Schepman,, Bankia campanellata Moll and Roch. The need for improving the durability of rubber wood by suitable preservation techniques for its potential use in various marine constructions is presented and highlighted.
Keywords: Rubberwood; Rubberwood durability